The Karoo : ecological patterns and processes - Dean, W. Richard J. (William Richard John), 1940-; Milton, Suzanne J. (Suzanne Jane), 1952- (Cambridge University Press, 1999)
A comprehensive synthesis of ecological studies of this unique southern African biome, presenting information on biogeographic patterns and life processes, form and function of animals and plants, foraging ecology, landscape-level dynamics and anthropogenic influences.